Application of DNA-based forensic analysis for the detection of homologous transfusion of whole blood and of red blood cell concentrates in doping control. (August 2016) - Stampella, Alessandra; Di Marco, Sabrina; Pirri, Daniela; de la Torre, Xavier; Botrè, Francesco; Donati, Francesco
Graphical abstract: Homologous blood transfusions, a form of "blood doping" in sport, can be detected by forensic genetic techniques based on DNA typing. The proposed procedure, that tested effective also on mixed samples of red blood cell concentrates, allows to correctly identify also those samples that would have given a false-negative result if assayed by the reference cytofluorimetric technique. Highlights: Forensic genetics techniques are proposed to detect homologous blood transfusions. The proposed method, based on DNA typing, tested effective on ex vivo blood mixtures. Mixed blood samples are revealed by triplets and quadruplets at one or more loci. The same procedure can be applied also to red blood cell concentrates. Abstract: In this work we present the application of a method for the identification of homologous blood transfusions using forensic genetic techniques based on DNA typing. Ex vivo mixtures of human blood samples – either whole blood or red blood cell concentrates – simulating homologous blood transfusions at different percentages of the donor were typed for a panel of 16 highly variable DNA short tandem repeats (STR). Tested samples included also mixtures, which gave false-negative results if assayed by the reference flow cytofluorimetric method, which is based on the recognition of target antigens located on the membrane of the red blood cell. The recognition of triplets and quadruplets at various loci gave information of the presence of cells belonging to different individuals, as it is the case for homologous blood transfusions. Specificity and sensitivity of the method were assessed in the validation study. The method proved to be unequivocally specific since it was able to recognize all single profiles of each individual, clearly discriminating them from mixtures. Sensitivity resulted as a consequence of the percentage of the donor aliquot in the total volume of the mixture. Although the source of DNA in a blood sample is represented only by nucleated white blood cells, the same procedure resulted effective also in detecting mixtures of red blood cell concentrates (RBCC) from leukodepletion procedure: DNA of the donor from the residual white blood cells resulted still detectable, even if with an expected loss of sensitivity. The proposed approach may contribute to reduce the risk of false-negative results, which may occur using the reference cytofluorimetric method.